The Possible Relation between Pityriasis Alba and Intestinal Parasitic Infestation Among Children in Tikrit City, A Case Control Study - Asaf Kamal Asaad Taha1 , Mazin Hamid Ayyash2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: There is a solid belief stated that the appearance of hypopigmented patches on childrenface is a sign of their helminthic or parasitic intestinal infestation despite the constant health educationabout the absence of such relation. Pityriasis Alba (PA) is common benign skin lesion characterized byfine scaly hypopigmented patches (HP) or macules (1) mostly in the face and upper body parts. (2-4) PAmay be atopic dermatitis related or endemic PA. PA occurs mostly in 3-16 years old children and accountsof 5% of pediatric population worldwide. Prevalence rate in Iraq is high (38.2%). No specific cause ofPA has been identified. Diagnosis of PA depends on the clinical picture and treatment may implicatesunscreen and topical corticosteroids despite its self-limiting privilege. Helminthiasis (worm infestation)is the hosting of parasitic worms after invading humans and other animals necessarily to complete theirlifecycle. Enterobius vermicularis is the most common helminthic intestinal infestation among children inIraq. The main complaint of helminthiasis is the perianal itching, especially at bed time. The study aims todetermine the relation of intestinal helminths with PA. Study Design: This prospective and a case-controlstudy had consisted of 43 males (53.5%) and females (46.5%) children of 5-15 years of age presented withHP. Results and Discussion: 4 (9.3%) cases presented with Enterobius vermicularis given antihelminthicdrugs and had their infestation eradicated completely after a week. 39 (90.7%) children presented with noinfestation, regarded as control group, and so given placebo treatment. Number and size of HP varied afterthe 6 weeks of treatment. Although cases shown more numerous (6.0 ± 2.9) HP and larger size (120.0 ± 72.2)than control group (4.9 ± 3.6 and 90.0 ± 58.3 respectively), but the difference was not significant for bothgroups (cases and control) and between them for both HP number and sizes (p>0.6). Conclusion: There isno enough prove of the relationship between children intestinal parasitic infestation and the appearance ofhypopigmented patches.